Performance comparison of 2-1-3, 1-3 and 1-3-2 piezoelectric composite transducers by finite element method - Sun, Y.; Hua, B. (Condensed Matter Physics, 2018)
1-3 type, 1-3-2 type and 2-1-3 type piezoelectric composites are three proper smart materials for the design and manufacture of ultrasonic transducers. They have been proposed in different stages but possess similar properties. Compared with the initial 1-3 type composite, 1-3-2 composite is of higher mechanical stability. Compared with 1-3-2 composite, 2-1-3 composite has lower manufacturing difficulty. In this paper, a comparative study on these three composites in terms of receiving transducer material properties is presented. Finite element method (FEM) has been adopted to calculate longitudinal velocity, thickness electromechanical coupling coefficient and voltage receiving sensitivity. It is concluded that for a large aspect ratio α = 1, the performance of 2-1-3 composite transducer is much better than that of 1-3 and 1-3-2 composite transducers. The thickness electromechanical coupling coefficient of 2-1-3 composite transducer is about 5.58 times that of 1-3 composite transducer and 7.42 times that of 1-3-2 composite transducer. The voltage receiving sensitivity at 2 kHz of 2-1-3 composite transducer is 13.1 dB higher than that of 1-3-2 composite transducer and 12.3 dB higher than that of 1-3 composite transducer.